Problem questions of scientific support of service and combat activities of law-enforcement forces - Kuznichenko S. О. (Honor and Law, 2019)
This article deals with separate questions of expansion of scientific branches namber within the scientific speciality “Service-combat activity of law-enforcement forces”.